Response time to stimuli in Division I soccer players - Spierer, D. K.; Petersen, R. A.; Duffy, K. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this investigation was to examine the effect of auditory stimuli (AS) and visual stimuli (VS) on sprint time, sprint speed, and reaction time in National Collegiate Athletic Association Division I male soccer players. Fifteen healthy subjects (mean age 22.1 ± 1.6 years) volunteered for the study. This experiment was conducted on a regulation soccer field, using a wireless timing system. Subjects stood on a touch-and-release pad and were instructed a prompt (AS: "go" command via a microphone interface, VS: movement of a player located 10 m from the start) to run 20 m through the finish line timing gates without decelerating. After 3 submaximal sprint trials at 50%, conditions (AS and VS) were randomized and performed 3 times by each subject. The best sprint time, sprint speed, and reaction time were recorded. Paired t-tests were conducted on dependent variables to determine statistically significant differences. An alpha level was set at p = 0.05. Sprint time was reduced in response to VS as compared to AS (3.76 ± 0.16 seconds vs. 3.85 ± 0.15 seconds, p = 0.001). Sprint speed (distance covered) was greater in VS compared to AS (5.3 ± 0.21 m/s vs. 5.1 ± 0.19 m/s, p < 0.001), and reaction time was reduced in VS compared to AS (0.53 ± 0.048 seconds vs. 0.61 ± 0.044 seconds, p = 0.001). These data show that VS rather than AS improve sprint response times in collegiate male soccer athletes. The data suggest that performance on the field may be improved if coaches and players strategize to integrate visual cues (e.g., gestures and signals) during practices and games.